How does Citizen Science matter for policy? Analyzing the impact of citizen science in policy making - Almomani, Abeer; Awai, Erdoo Paula; Bonn, Aletta; de Barros, Ingrid Almeida; Friedly, Colleen; Gharesifard, Mohammad; Hecker, Susanne; Kartika, Erlinda Cahya; Kraft, Anne; Matthus, Elsa; Peter, Maria; Raja Schoob, Nussaibah Begum; et al. (iDiv Annual Conference 2019, 2019)
Citizen Science has been proven to support policy making (Bio Innovation Service, 2018),yet harnessing the full potential of Citizen Science requires further understanding of the particular areas of the policy development process where different Citizen Science projects have contributed. Using the policy cycle framework (Howlett&Ramesh, 2003) we assessed 500 Citizen Science projects reported in EU inventory and conducted in-depth analysis of 25 case studies. Our study aims to determine the impact of citizen science projects on the policy cycle.<br